Genetic Risk Scores Identify Genetic Aetiology of Inflammatory Bowel Disease Phenotypes - Voskuil, M D (J Crohns Colitis, 2020)
BACKGROUND AND AIMS: Inflammatory bowel disease [IBD] phenotypes are very heterogeneous between patients, and current clinical and molecular classifications do not accurately predict the course that IBD will take over time. Genetic determinants of disease phenotypes remain largely unknown but could aid drug development and allow for personalised management. We used genetic risk scores [GRS] to disentangle the genetic contributions to IBD phenotypes. METHODS: Clinical characteristics and imputed genome-wide genetic array data of patients with IBD were obtained from two independent cohorts [cohort A, n = 1097; cohort B, n = 2156]. Genetic risk scoring [GRS] was used to assess genetic aetiology shared across traits and IBD phenotypes. Significant GRS–phenotype (false-discovery rate [FDR] corrected p <0.05) associations identified in cohort A were put forward for replication in cohort B. RESULTS: Crohn’s disease [CD] GRS were associated with fibrostenotic CD [R(2) = 7.4%, FDR = 0.02] and ileocaecal resection [R(2) = 4.1%, FDR = 1.6E-03], and this remained significant after correcting for previously identified clinical and genetic risk factors. Ulcerative colitis [UC] GRS [R(2) = 7.1%, FDR = 0.02] and primary sclerosing cholangitis [PSC] GRS [R(2) = 3.6%, FDR = 0.03] were associated with colonic CD, and these two associations were largely driven by genetic variation in MHC. We also observed pleiotropy between PSC genetic risk and smoking behaviour [R(2) = 1.7%, FDR = 0.04]. CONCLUSIONS: Patients with a higher genetic burden of CD are more likely to develop fibrostenotic disease and undergo ileocaecal resection, whereas colonic CD shares genetic aetiology with PSC and UC that is largely driven by variation in MHC. These results further our understanding of specific IBD phenotypes.